Haroldo de Campos: um caso concreto-barroco - Campos, Raquel (eLyra, 2021)
This research aims to analyze the poetic writing of Haroldo de Campos, which brings a baroque language closer to a concrete language, exemplifying this supposed paradox through the poem A Máquina do Mundo Repensada. Augusto de Campos, his brother, defined him as a kind of “concrete-baroque”, capable of bringing together these two apparently contradictory facets in his production. The defense of the inclusion of the Brazilian baroque in the formation of national literature made by Haroldo also reverberated in his work, leaving baroque traces in his writings, as will be shown below. Finally, the analyzes made in this article will lead us to an analog and iconic reading gesture, prioritizing the similarities brought by the analogies, which will allow us to conceive the existence of opposite paths shared in the same text.